Is the rod necessary? Biomechanical comparison of static knee spacers during axial loading. (January 2023) - Egenolf, Philipp; Wasseq, Dorothee; Scheyerer, Max Joseph; Prescher, Andreas; Wegmann, Kilian; Müller, Lars Peter; Eysel, Peer; Otto-Lambertz, Christina
Abstract: Background: Knee Spacers are required in two-stage revision surgery of periprosthetic joint infection of the knee. Extended bone and ligamentous defects are often temporarily arthrodised via a static spacer. Regarding their weight-bearing potential and construction, there is no current consent. Our aim was to evaluate three individual static spacer variants with regard to their axial loading capacity. Methods: The static spacer variants were tested in a cadaver model. One after the other, a spacer with metal-reinforced rods, a spacer without metal reinforcement and a rod-less spacer were implanted and tested up to an axial loading of 1000 Newton. Target parameters were plastic deformation, stiffness and spacer movement at both the femoral and tibial surface. Loading was applied up to 1000 Newton. Radiological controls of the bone substance were performed. Findings: The spacer variants did not differ regarding deformation, stiffness or spacer movement. However, deformation increased significantly with the axial load in all spacer variants. Radiographs showed no fracture or spacer-dislocation resulting from testing. Interpretation: While the spacer reinforcement or the sheer presence of a rod did not influence the axial loading capacity in this in vitro study, weightbearing should be discouraged to limit further bone erosion. Highlights: Intramedullary rods do not increase axial loading capacity of static knee spacers. Increased axial loading results in higher deformation. Full weight bearing on static knee spacers should be discouraged.